2013
DOI: 10.1111/ases.12049
|View full text |Cite
|
Sign up to set email alerts
|

Experience with laparoscopic treatment for paraesophageal hiatal hernia

Abstract: Laparoscopic surgery for paraesophageal hiatal hernia is safe and effective with minimal morbidity and early recovery. However, it is important to determine the appropriate timing of surgery based on the severity of the hernia and the patient's general status and comorbidities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Recently, LNF has become a standard surgical treatment for PEH (5). Nguyen et al retrospectively compared 2069 laparoscopic repair procedures and 657 open repair procedures for PEH (6), and found that the laparoscopic approach was associated with a shorter hospital stay, less need for intensive care unit placement, fewer overall complications and 30-day readmissions, and lower costs.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, LNF has become a standard surgical treatment for PEH (5). Nguyen et al retrospectively compared 2069 laparoscopic repair procedures and 657 open repair procedures for PEH (6), and found that the laparoscopic approach was associated with a shorter hospital stay, less need for intensive care unit placement, fewer overall complications and 30-day readmissions, and lower costs.…”
Section: Discussionmentioning
confidence: 99%